The use of hydrogen cyanamide or nitrogen fertilizer increases vegetative and productive performance of fig cv. Roxo de Valinhos - Azevedo Souzar, Jackson Mirellys; Silva, Marcelo de Souza [UNESP]; Ferraz, Rafael Augusto [UNESP]; Modesto, Joyce Helena [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Batista Bolfarini, Ana Carolina [UNESP]; Tecchio, Marco Antonio [UNESP]; Leonel, Sarita [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2021)
Some plants do not demand a lot of chilling hours, but methods to overcome dormancy promote more vigorous and productive plant. This study aimed to assess hydrogen cyanamide and nitrogen fertilizer with different concentration to growth and production in 'Rom) de Valinhos' fig tree. Two crop cycles (2015/2016 and 2016/2017) was performed in Sao Manuel city, Sao Paulo State, Brazil. Phenological and productive data was evaluated in a 2 x 5 factorial (Product x Concentration), organized in randomized complete block design, with three trees by plot. The factor products had as level hydrogen cyanamide and nitrogen fertilizer and the factor concentrations was constituted by 0, 1, 2, 3, and 4%. Furthermore, the following data was evaluated: number of days for budbreak, number of buds per plant, harvest period, branch length and diameter, leaf number, leaf area, number of fruits per plant, fruit mass, production and yield. Results indicated that both products anticipated the sprouting and promoted a higher number of buds overcome the dormancy. Plant production was higher in both cycles when the products were used (2.1 and 2.7, respectively). At last, hydrogen cyanamide showed better outcomes due to the higher number of fruits and production.
Keywords: Ficus carica L.; phenology; plant growth regulator; sprouting; overcome dormancy; yield